Diagnosis and Surgical Repair for Coarctation of the Aorta With Intracardiac Defects: A Single Center Experience Based on 93 Infants - Wu, Yuhao; Li, Jiashan; Wu, Chun; Zhu, Jin; He, Ling; Feng, Chuan; Yang, Yiting; Jin, Xin (Frontiers in Pediatrics, 2020)
Introduction This study aims to summarize the clinical characteristics of coarctation of the aorta (CoA) associated with intracardiac anomalies in infants. Methods Medical records of 93 infants who were diagnosed with CoA and intracardiac anomalies from August 2009 to August 2018 were retrospectively reviewed. Results All of the 93 infants underwent single-stage repair for CoA associated with intracardiac anomalies. Mean operative time was 264.6±57.1 minutes, and the time of ICU stay was 7.0±4.1 days. The residual transcoarctation pressure gradient before discharge was lower than the pressure gradient prior to surgery (48.3±17.5 vs 22.4±9.6mmHg, P<0.01). Early death before discharge was found in 5 infants. The mean follow-up time of 88 hospital survivors was 40.0±26.4 months, and no subsequent death occurred in the follow-up. Transcoarctation pressure gradient of 88 survivors in their last follow-up was 19.6±10.5mmHg. Pressure gradient of 27 cases was higher than 20 mmHg. Significant lower limbs retardation was observed in 4 cases, therefore, balloon angioplasty consult was recommended. The cumulative recoarctation-free survival rate in 3-year follow-up was 73.5%. Conclusions To avoid secondary operations in early period, single-stage repair of CoA associated with intracardiac anomalies was effective and safe, and the outcomes in early to mid-term follow-up were satisfactory.